Model of energy security applied to Latin American countries - Saravia, Fredy (2015)
Between energy policy has become increasingly important the notion of "energy security", that is, ensuring the continued availability of energy, in various forms, quantities and at affordable rates. The concept of energy security has evolved from its unique combination of oil supply, to incorporate environmental and social concepts related to energy. In Latin American countries energy security continues to be a matter of national policy, in this context, it is necessary to quantify the concept of "energy security" and adapt to national needs and possibly the Latin American reality in order to have a model to serve as a tool for planning long-term energy policy. In this paper, proposed a quantitative model for an index of energy security, this model are applied for the Latin American countries whose results are compared with similar research of the World Economic Forum.